2019
DOI: 10.34133/2019/1748489
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Ultrasound Deep Brain Stimulation for the Treatment of Parkinson’s Disease Model Mouse

Abstract: Modulating basal ganglia circuitry is of great significance in the improvement of motor function in Parkinson’s disease (PD). Here, for the first time, we demonstrate that noninvasive ultrasound deep brain stimulation (UDBS) of the subthalamic nucleus (STN) or the globus pallidus (GP) improves motor behavior in a subacute mouse model of PD induced by 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP). Immunohistochemical c-Fos protein expression confirms that there is a relatively high level of c-Fos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 64 publications
0
47
0
Order By: Relevance
“…However, apomorphine is a remarkable drug that is extensively used for stimulating motor functions in PD. Non-pharmacological treatments like deep brain stimulation and acupuncture have been used to improve motor function in PD patients [ 133 , 156 ]. In accordance with the above-cited literature, the midforebrain lesion type is more effective in causing neurodegeneration and the symptoms compared to other administrative methods in animal models of PD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, apomorphine is a remarkable drug that is extensively used for stimulating motor functions in PD. Non-pharmacological treatments like deep brain stimulation and acupuncture have been used to improve motor function in PD patients [ 133 , 156 ]. In accordance with the above-cited literature, the midforebrain lesion type is more effective in causing neurodegeneration and the symptoms compared to other administrative methods in animal models of PD.…”
Section: Discussionmentioning
confidence: 99%
“…Subthalamic nucleus/globus pallidus-ultrasound deep brain stimulation increased the latency to fall in the rotarod test on the 9th day and reduced the pole test time on the 12th day. Their data also showed that the ultrasound deep brain stimulation protected the dopaminergic neurons by reducing antiapoptotic expression [ 156 ]. The drug dose, lesion type, and behavioral evaluating methods in each MPTP-induced PD animal model are summarized in Table 3 .…”
Section: Neurotoxins Used To Induce Pd In Vivo Modelsmentioning
confidence: 99%
“…Because of their high genomic homology and similar anatomical eye structure and ontogenetic development of the fovea to humans, rhesus macaques present great potential as models for studying OCA and other neurological disorders [32,33,[37][38][39][40]. In this study, we identified rhesus macaque models that were characterized by classical ocular characteristics comparable to those of OCA patients, including nystagmus, retinal hypopigmentation, and foveal hypoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Implanted probes delivering focal cooling or heating have been demonstrated to decrease or respectively increase the excitability of surrounding cortical structures (Chen et al 2015;Fujioka et al 2010). Focused ultrasound can be delivered non-invasively via wearable probes and has been shown to modulate neural activity in basal ganglia in mice (Zhou et al 2019). Optogenetic stimulation without penetrating optical probes has also been recently made possible using nanoparticle mediated upconversion of infrared light (Chen et al 2018).…”
Section: Future Directions: Multimodal Neural Systems For Addiction Tmentioning
confidence: 99%